Pengaruh Terapi Mindfulness Spritual Dengan Peningkatan Efikasi Diri Dalam Management Marah Pendamping Odha Di Puskesmas Putri Ayu Kota Jambi - Yuliana, Yuliana -; Yesni, Marnila; Dwiyanti, Rahmi; M, Rino; Al-fajri, Jufri (Universitas Baiturrahim, 2024)
ODHA are people with HIV (Human Immunodeficiency Virus) and AIDS (Acquired Immuno Deficiency Syndrome). Changes in the character of ODHA cannot be separated from psychological and social pressure and make many ODHA become depressed. The psychological and social pressure experienced by ODHA also has a negative emotional impact. Most people are familiar with the term emotions related to anger and hatred. ODHA companions are ODHA and are an extension of nurses and even foundations in their approach to ODHA. This research was conducted at the Putri Ayu Community Health Center which is a partner location of STIKBA Jambi. This research design uses a quasi-experimental research design (pre and posttest without control group design). There were 12 participants, sampling was total sampling. The research instrument used a pre-test and post-test questionnaire via Google Foam and sent a spiritual mindfulness video via a link. The research results showed that there was an effect of spiritual mindfulness therapy on the belief of being able to overcome anger and negative feelings with a p-value <0.042, an influence of spiritual mindfulness therapy on the belief of being able to overcome sadness when in trouble with a p-value <0.003, the effect of spiritual mindfulness therapy on confidence able to avoid losing control when angry with a p-value <0.042. The output of this research is national publications